Health disparities and determinants of health: A glance at Healthy People 2020 goals - Velis, Evelio; Hernandez-Pupo, Nora; Borras, Selene (European Scientific Journal, ESJ, 2020)
Introduction: Adverse health outcomes are often used as indicators of the health of a nation and are generally better in developed countries. According to the World Health Organization, every day, about 800 women died due to complications of pregnancy and child birth. Almost all of these deaths occurred in low-resource settings, and most could have been prevented. Maternal mortality ratio in the United States in 2015 was 14 maternal deaths per 1000 live births, range, significantly higher than most developed countries including Sweden (4 per 1000 live births), Switzerland (4 per 1000 live births), Austria (4 per 1000 live births), Japan (5 per 1000 live births), Germany (6 per 1000 live births), Canada (7 per 1000 live births), France (8 per 1000 live births), United Kingdom (9 per 1000 live births). Methods: Health outcomes were collected from the Centers for Disease Control and Prevention while socio-economic related indicators were extracted from the US Census Bureau. Selected health outcomes in the study are: infant and fetal mortality, maternal mortality, life expectance and cancer. Socio-economic indicators such as poverty and health insurance coverage were also analyzed. An evaluation of health disparities among racial and ethnic groups was performed. Correlation analyses were conducted to explore the potential strength of the relationship between health outcomes and socioeconomic factors in the US at the state level. Conclusion: Health disparities are still a major public health problem in US. A strong correlation at the state level between health outcomes and poverty and health insurance coverage at the state level was identified.